2011
DOI: 10.1074/jbc.m110.217836
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Antagonism between Tumor Suppressor Protein p53 and Fortilin, an Anti-apoptotic Protein

Abstract: Tumor suppressor protein p53, our most critical defense against tumorigenesis, can be made powerless by mechanisms such as mutations and inhibitors. Fortilin, a 172-amino acid polypeptide with potent anti-apoptotic activity, is up-regulated in many human malignancies. However, the exact mechanism by which fortilin exerts its anti-apoptotic activity remains unknown. Here we present significant insight. Fortilin binds specifically to the sequence-specific DNA binding domain of p53. The interaction of fortilin wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 69 publications
0
60
0
Order By: Relevance
“…Indeed down-regulation of TCTP through activation of a (temperature-sensitive) mutant protein of p53 (Tuynder et al 2002;Bommer et al 2010) was an initial observation in this context. The mutual antagonism between p53 and TCTP was then described by three groups in brief succession (Amson et al 2012;Chen et al 2011;Rho et al 2011). The underlying mechanisms involved in this included the following:…”
Section: Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed down-regulation of TCTP through activation of a (temperature-sensitive) mutant protein of p53 (Tuynder et al 2002;Bommer et al 2010) was an initial observation in this context. The mutual antagonism between p53 and TCTP was then described by three groups in brief succession (Amson et al 2012;Chen et al 2011;Rho et al 2011). The underlying mechanisms involved in this included the following:…”
Section: Stress Responsementioning
confidence: 99%
“…However, one of these anti-apoptotic mechanisms ought to be mentioned here, i.e. the antagonism of TCTP to the tumour suppressor protein p53, which is crucial for TCTP to exert its cancer-promoting activity (Amson et al 2012;Chen et al 2011). The cytoprotective role of TCTP in cancer cells is well documented, for example in conditions of oxidative stress (Lucibello et al 2011), or of treatment with various anticancer drugs, the latter often resulting in chemoresistance of these cells (Li et al 2001;Jung et al 2014;Graidist et al 2004;Bommer et al 2017;He et al 2015), which is a frequent problem in cancer chemotherapy.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 99%
“…Rho et al [57] showed that overexpression of TCTP in lung carcinoma cells reversed p53-mediated apoptosis, whereas TCTP knock-down increased apoptosis. Similarly, Chen and colleagues [58] observed TCTP (fortilin) interaction with p53 using GST-pull down assays; they showed that TCTP inhibits p53-dependent apoptosis. However, these two studies arrive at differing conclusions in the following two points: 1.…”
Section: + -Atpasementioning
confidence: 99%
“…2. In the mechanism by which TCTP antagonises p53: Rho et al reported that TCTP is destabilising p53 in lung cancer cells, whereas Chen and colleagues did not observe p53 destabilisation, but instead proposed that TCTP blocks p53-induced transcriptional activation of Bax [58].…”
Section: + -Atpasementioning
confidence: 99%
See 1 more Smart Citation